Combined Lysis of Thrombus with Ultrasound and Systemic Tissue Plasminogen Activator for Emergent Revascularization in Acute Ischemic Stroke (Clotbust-ER): Design and Methodology of a Multinational Phase 3 Trial. Issue 7 (October 2015) - Schellinger, Peter D.; Alexandrov, Andrei V.; Barreto, Andrew D.; Demchuk, Andrew M.; Tsivgoulis, Georgios; Kohrmann, Martin; Alleman, John; Howard, Virginia; Howard, George; Alexandrov, Anne W.; Brandt, Gordon; Molina, Carlos A.
Background: We designed a Phase 3 clinical trial to determine the safety and efficacy of adding transcranial ultrasound using an operator-independent headframe to recombinant tissue-plasminogen-activator for the treatment of acute ischemic stroke. Methods: Combined lysis of thrombus with ultrasound and systemic tissue-plasminogen-activator for emergent revascularization in acute ischemic stroke is a randomized, double-blind, placebo-controlled clinical trial that will enroll subjects with the following main inclusion criteria: less than 4·5 hours from symptom onset (three-hours in US and Canada), age 18–80 years, baseline National Institutes of Health Stroke Scale score ≥ 10, and premorbid modified-Rankin-score of 0–1, eligibility for full dose recombinant tissue-plasminogen-activator. Subjects will receive two-hours of 2-MHz pulsed wave transcranial ultrasound (target group) or sham ultrasound (control group). The projected sample size is approximately 824 subjects. Results: The primary endpoint, based on intention-to-treat criteria of patients enrolled within three-hours of symptom onset is the comparison between target and control groups of modified-Rankin-score scores at day 90 poststroke assessed using the proportional odds method. The study will have two planned interim analyses after approximately one-third and two-thirds of subjects have reached the 90-day modified-Rankin-score evaluation. Safety outcomes are symptomatic intracranial hemorrhage within 24 h and an overall analysis of adverse events. Conclusions: Since intravenous recombinant tissue-plasminogen-activator remains the only medical therapy to reverse ischemic stroke applicable in the emergency department, our trial will determine if the additional use of transcranial ultrasound improves functional outcomes in patients with severe acute ischemic stroke (NCT#01098981).